2017
DOI: 10.1177/1559325817739760
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Regulation of Mouse Embryonic Stem Cell Proliferation by Nicotine Is Mediated Through Wnt Signaling Pathway

Abstract: Introduction:Nicotine is a key biologically active compound of cigarettes. Although nicotine is a risk factor for various health issues, it may also be beneficial when treated at moderate concentrations. Nicotine has been shown to bidirectionally regulate stem cell proliferation and differentiation depending on the doses applied. It is not clear whether or how nicotine regulates mouse embryonic stem cell (mESC) survival and proliferation.Methods:Mouse embryonic stem cells were cultured in the presence of 0.01,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Nicotine reduced the proliferation of human Wharton’s jelly mesenchymal stem cells [ 69 ], rat microglia [ 70 ] and periodontal ligament-derived stem cells [ 71 ]; it caused autophagy in the Leydig cells [ 72 ] and pyroptosis of human aortic endothelial cells (HAECs) [ 73 ]. Nicotine affects embryonic mouse stem cells in two ways: at low concentrations (0.01 and 0.1 μM) it stimulates, while at high concentrations (1 and 10 μM) it suppresses proliferation without affecting viability [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine reduced the proliferation of human Wharton’s jelly mesenchymal stem cells [ 69 ], rat microglia [ 70 ] and periodontal ligament-derived stem cells [ 71 ]; it caused autophagy in the Leydig cells [ 72 ] and pyroptosis of human aortic endothelial cells (HAECs) [ 73 ]. Nicotine affects embryonic mouse stem cells in two ways: at low concentrations (0.01 and 0.1 μM) it stimulates, while at high concentrations (1 and 10 μM) it suppresses proliferation without affecting viability [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of current study, it seems that CSC exhibit hormetic dose responses on behaviors of 2‐C57 and 6‐C57 cells including proliferation, DT, Bax/Bcl2 ratio, Bax , Bcl2, and Ahr expression. Studies have shown that nicotine display biphasic dose response on mESC proliferation …”
Section: Discussionmentioning
confidence: 99%
“…More than 8 million people die from tobacco use each year [ 62 ]. Previous studies have indicated that nicotine exhibits dose-dependent bidirectional regulation of mouse [ 63 ] and rat [ 64 ] stem cell proliferation. Moreover, long-term and/or continuous nicotine administration has been reported to have a deleterious effect on ischemic brain injury [ 65 ].…”
Section: Discussionmentioning
confidence: 99%